Peran Strategi Pembelajaran Reflektif dalam Menumbuhkan Kesadaran Religius Siswa - Yogi Tri Gustian; Zul Hafriadi Rahmat; Gusmaneli Gusmaneli (Jurnal Pendidikan Dirgantara, 2025)
This study discusses the role of reflective learning strategies in fostering students' religious awareness, with a focus on Islamic character education. Using the literature review method, this research collects and analyzes relevant literature on reflective learning, Islamic religious education, and Islamic character. The findings indicate that reflective learning strategies can bridge the gap between religious knowledge and students' daily actions, while strengthening their Islamic character through deep introspective processes. This strategy provides students with the opportunity to reflect and evaluate their experiences, leading to the reinforcement of spiritual and moral values in their lives. However, challenges in its implementation, such as teacher readiness and classroom culture, need to be addressed for optimal application. The implications of this study emphasize the importance of integrating reflective learning in Islamic character education to shape a generation that is not only intellectually capable but also morally virtuous.